Medical Topic in Nominative Models of Mineralogical Vocabulary - Kuchko, Valeria S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2025)
This article continues the motivational study of the Russian and foreign-language mineralogical names, initiated in recent years by the Ural School of Onomastics, Etymology, and Ethnolinguistics. The article focuses on a separate group of mineralogical vocabulary that functions in the Russian language, i.e. names that are motivationally related to the vocabulary of the medical thematic field. The purpose of the article is to trace the nomination motives characteristic of this group and identify the naming patterns used within it. The group is formed by means of both official and unofficial terminology (namely, terminology belonging to the professional jargon of those who mine, process, and sell minerals). There are original names, loanwords, and calques. The sociolinguistic heterogeneity of the linguistic facts considered in the work shows the difference in the embodiment of the medical topic by means of different linguistic strata. The author demonstrates that the medical topic is represented by various nominative features. The name can be based on a general motive, such as “a stone has medicinal properties” (камень медика, камень здоровья, etc.) / “medical functions” (аптекарский камень); a motive for providing medical care to a specific organ (нефрит, почечный камень, жад) or getting rid of a certain condition (аметист); “the stone is sick / healing” motive. The medical topic is also implemented in a naming pattern, according to which the name of a mineral or rock includes, for various reasons, the name of a disease (оспенная руда). The article traces the history of certain mineralogical names (in particular, аптекарский камень ‘serpentine,’ нефрит, почечный камень ‘jade’, жадеит) in the Russian language tradition against the background of a foreign language.